IMPACT OF CONSTRUCTION INVESTMENT ON THE UNEMPLOYMENT RATE IN NIGERIA - Saka, Najimu; Moyanga, Dorcas Titilayo (Journal of Surveying, Construction and Property, 2024)
Nigeria being an export-driven economy with a primary focus on oil and gas has a high rate of unemployment. However, the construction industry as a labour-intensive economic sector may provide the prospect for full employment. Hence, this study investigates the effect of construction sector investment on the unemployment rate. Time series data was extracted from the World Bank’s World Development Indicators (WDI) for the years 1991 through 2020. The study adopted multiple regression and Autoregressive Distributed lag (ARDL) models for analyzing the data. From the result, the models' estimate indicates that the only significant predictor of the current unemployment rate is the lagged unemployment of the previous year. Both the construction investment growth rate and the rate of economic growth do not have a substantial effect on the current unemployment rate which is contrary to Okun’s law. Based on the findings, this study recommends diversification of the economy in favour of labour-intensive sectors like construction and manufacturing for sustainable solutions to unemployment in Nigeria.